Empirical study of elastic properties of BX (X = As, Sb) materials - Daoud, Salah (International Journal of Scientific World, 2015)
The principal goal of this work is the prediction of elastic properties of Boron-Arsenide (BAs) and Boron- Antimonide (BSb) materials by means of some emperical formulas and with the help of two experimental physical quantities (the bond length and the bulk modulus which are taken from the literature for BAs material and the bond length only for BSb material). The homopolar and heteropolar energies, the bonding-antibonding energy gap, the covalency, the elastic constants, the Kleinman parameter, the Cauchy discrepancy in elastic constant, the Cauchy coefficient, the Born ratio, the cohesive energy and finally the Knoop microhardness are predicted and analyzed in comparison with the available theoretical data of the literature. Our obtained results are in general in agreement with other previous theoretical data.